Ember-months and disaster beliefs in Nigeria (2011)
Local government administration is widely regarded as government closest to the people of the grassroot. It performs vital functions such as: political education, mobilization of the people for popular participation in governance, vehicle for political accountability, among others. The struggle to bring about a local government system in Nigeria has been a long drawn one. Efforts have geared towards moving the system from local administration to local government with functional political and economic autonomy. Yet, local government administration is confronted with issues and challenges such as: federal and state government’s interventions in the constitutional apportioned responsibilities of local government. The paper argues that for local government administration to realize its lofty goals, the country should return to true federalism, enthrone positive leadership, pursuit of economic self-reliance through internally generated revenue, and embrace attitudinal and behavioural changes to achieve good governance.